2016
DOI: 10.1103/physrevx.6.041024
|View full text |Cite
|
Sign up to set email alerts
|

Low-Noise Amplification and Frequency Conversion with a Multiport Microwave Optomechanical Device

Abstract: High-gain amplifiers of electromagnetic signals operating near the quantum limit are crucial for quantum information systems and ultrasensitive quantum measurements. However, the existing techniques have a limited gain-bandwidth product and only operate with weak input signals. Here we demonstrate a two-port optomechanical scheme for amplification and routing of microwave signals, a system that simultaneously performs high-gain amplification and frequency conversion in the quantum regime. Our amplifier, implem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 46 publications
2
76
0
Order By: Relevance
“…Similar noise suppression in reciprocal optomechanicalbased amplifiers was found in Refs. [23,26] and was also reported in recent experiments [27,28].…”
Section: A Unresolved-sideband (Usb) Amplificationsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar noise suppression in reciprocal optomechanicalbased amplifiers was found in Refs. [23,26] and was also reported in recent experiments [27,28].…”
Section: A Unresolved-sideband (Usb) Amplificationsupporting
confidence: 77%
“…Clearly, the same "dissipative" amplifier could be realized in the resolved-sideband regime, i.e., with two independent modes,d 1 andd 2 . Based on such a three-mode setup, a recent experiment showed that broadband amplification close to the quantum limit is possible [27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these amplifiers are currently actively used in quantum science. Also electromechanical systems have been investigated to this end [11][12][13][14][15]. In recent work, Refs.…”
mentioning
confidence: 99%
“…In recent work, Refs. [14,15] demonstrate a phase-insensitive amplifier with a noise relatively low but not quite yet at the quantum limit.…”
mentioning
confidence: 99%
“…Transfer of both negativity and non-Gaussianity is much more demanding than the transfer of Gaussian entanglement. We verify that the electromechanical platforms930 with microwave radiation are already feasible for such transduction preserving negativity of Wigner function. The optomechanical experiments require coupling higher than critical to reach this possibility.…”
mentioning
confidence: 55%